Pemberdayaan Melalui Pengembangan Soft Skill Kewirausahaan Untuk Kemandirian Bagi Siswa Dewasa di Pusat Kegiatan Belajar Masyarakat Kinabalu Malaysia - susilo, heryanto; Widodo; Atmaja Johny Artha, I Ketut; Mustakim; Zakariyah, M Fahmi (JPUS: Jurnal Pendidikan Untuk Semua, 2025)
This study aims to explore the process of developing entrepreneurial soft skills as a strategy to increase the economic independence of adult students at the Community Learning Center (CLC) Kinabalu, Malaysia. The background of this study is limited access to formal education, low non-technical skills, and minimal entrepreneurial awareness among Package C students from families of Indonesian Migrant Workers (PMI). The study used a qualitative approach with an intrinsic case study design. Data were collected through in-depth interviews, participant observation during training, and document analysis. The intervention process was carried out online for four days with reference to the Asset-Based Community Development (ABCD) approach and andragogy principles. Data analysis was carried out using thematic analysis techniques to identify patterns of strengthening soft skills competencies including effective communication, adaptive leadership, creative problem solving, self- and time management, adaptation to change, emotional intelligence, results orientation, and networking. The results of the study revealed three main themes: (1) internalization of entrepreneurial values through experiential learning, (2) transformation of self-confidence into courage to start small businesses based on local resources, and (3) utilization of digital media as a means of developing business networks. This study concludes that strengthening local asset-based soft skills can shape entrepreneurial readiness in adult migrant communities, while also being a model that can be replicated in the context of non-formal education in border areas or other vulnerable communities.